Analisis Komparatif Financial Performance BPR dan BPRS Jawa Timur Sebelum dan Saat Pandemi Covid-19 - Amndana Widiyaningtias; Justita Dura (Politeknik Ganesha Medan, 2022)
During the COVID-19 epidemic, the financial performance of BPR and BPRS has decreased. The purpose of this study is to compare the financial performance of BPR and BPRS East Java before and moment the Covid-19 outbreak. Loan to deposit ratio (LDR), Return on Assets (ROA), Non-Performing Financing (NPF), Operating Expenses to Operating Income (OER), and Non-Performing Loan are all used to measure financial performance (NPL). Quantitative research methods with a comparative approach are applied in this research. Purposive sampling is a sampling technique for this research, including 28 BPRS companies and 271 East Java BPR companies in 2019-2020. Independent sample t-test regression is used to evaluate the data. The findings of this study showed that the variables of financial performance of OER and NPF in BPRS companies did not show significant differences, while the financial performance factors of NPL, ROA, and LDR in BPRS companies showed significant differences. The financial performance factors of ROA, LDR, and NPF in BPR companies are not really different, but the variables of financial performance of NPL and OER in BPR companies differ significantly.